A structured, blended learning program towards proficiency in epileptology: the launch of the ILAE Academy Level 2 Program. Issue 5 (3rd November 2022) - Blümcke, Ingmar; Biesel, Eva; Bedenlier, Svenja; Händel, Marion; Wilmshurst, Jo; Mehndiratta, Man Mohan; Yacubian, Elza Márcia; Cendes, Fernando; Arzimanoglou, Alexis; Beniczky, Sandor; Wolf, Peter; Giavasi, Christina; et al.
Abstract: The ILAE Academy is the online learning platform of the International League Against Epilepsy (ILAE) and offers a structured educational program addressing the competency‐based ILAE curriculum in epileptology. The platform was launched in July 2020 with a self‐paced course portfolio of interactive e‐learning modules addressing ILAE Level 1 learning objectives, defined as the entry level in epileptology. Using feedback questionnaires from completed Level 1 courses as well as sociodemographic and learning‐related data obtained from 47 participants, we show that over 50% of learners have an entry level in epileptology and do not have access to on‐site training and over 40% do not have access to on‐site training. Most respondents found the case‐based e‐learning modules relevant to their practice needs, and the time for completion was regarded as viable for most, reiterating the value of an online self‐paced training in the field. Participants who have successfully completed all compulsory e‐learning material of the Level 1 program and received their final certificate will now be eligible to subscribe to the Level 2 program. The Level 2 program addressing the proficiency level of the ILAE curriculum of epileptology was launched on the ILAE Academy platform in May 2022. The Level 2 program will offer an evolving series of self‐paced, interactive, case‐based e‐learning modules on diagnosis, treatment, and counseling of common as well as rare epilepsies at a higher level of care. An interactive online EEG and MRI reader was developed and is embedded into the course content to satisfy the demands of the learners. The hallmark of this level will be the blended learning with tutored online courses, e.g., the established VIREPA courses on EEG and the newly introduced VIREPA MRI program. Our distinguished faculty will hold live tutored online courses in small groups in various languages and continental time zones. Finally, the ILAE face‐to‐face curricular teaching courses at summer schools and congresses will represent another pillar of this advanced teaching level. The ILAE Academy will also provide Continuing Medical Education (CME) credits to support career planning in epileptology.